Enhancing efficacy of the MEK inhibitor trametinib with paclitaxel in -mutated colorectal cancer - Susmita Ghosh; Fan Fan; Reid Powell; Yong Sung Park; Clifford Stephan; E. Scott Kopetz; Lee M. Ellis; Rajat Bhattacharya (Therapeutic Advances in Medical Oncology)
Background: KRAS is frequently mutated in the tumors of patients with metastatic colorectal cancer (mCRC) and thus represents a valid target for therapy. However, the strategies of targeting KRAS directly and targeting the downstream effector mitogen-activated protein kinase kinase (MEK) via monotherapies have shown limited efficacy. Thus, there is a strong need for novel, effective combination therapies to improve MEK-inhibitor efficacy in patients with KRAS -mutated mCRC. Objective: Our objective was to identify novel drug combinations that enhance MEK-inhibitor efficacy in patients with KRAS -mutated mCRC. Design: In this study, we performed unbiased high-throughput screening (HTS) to identify drugs that enhance the efficacy of MEK inhibitors in vitro , and we validated the drugs’ efficacy in vivo. Methods: HTS was performed using three-dimensional CRC spheroids. Trametinib, the anchor drug, was probed with two “clinically ready” libraries of 252 drugs to identify effective drug combinations. The effects of the drug combinations on CRC cell proliferation and apoptosis were further validated using cell growth assays, flow cytometry, and biochemical assays. Proteomic and immunostaining studies were performed to determine the drugs’ effects on molecular signaling and cell division. The effects of the drug combinations were examined in vivo using CRC patient-derived xenografts. Results: HTS identified paclitaxel as being synergistic with trametinib. In vitro validation showed that, compared with monotherapies, this drug combination demonstrated strong inhibition of cell growth, reduced colony formation, and enhanced apoptosis in multiple KRAS -mutated CRC cell lines. Mechanistically, combining trametinib with paclitaxel led to alterations in signaling mediators that block cell-cycle progression. Trametinib also enhanced paclitaxel-mediated microtubule stability resulting in significantly higher defects in mitosis. Finally, the combination of trametinib with paclitaxel exhibited significant inhibition of tumor growth in several KRAS -mutant patient-derived xenograft mouse models. Conclusion: Our data provide evidence supporting clinical trials of trametinib with paclitaxel as a novel therapeutic option for patients with KRAS -mutated, metastatic CRC.